2022
DOI: 10.1371/journal.pone.0267413
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with change in adherence to COVID-19 personal protection measures in the Metropolitan Region, Chile

Abstract: Personal protective measures such use of face masks, hand washing and physical distancing have proven to be effective in controlling the spread of the Covid-19 pandemic. However, adherence to these measures may have been relaxed over time. The objective of this work is to assess the change in adherence to these measures and to find factors that explain the change For this purpose, we conducted a survey in the Metropolitan Region of Chile in which we asked the adherence to these measures in August-September 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Secondly, we explored whether people with different physical distancing behavior patterns differed with respect to sociodemographic characteristics. Multiple studies indicated that sociodemographic characteristics were associated with overall adherence to physical distancing guidelines, showing for instance that women, older people, and higher educated people were more likely to distance from others [ 6 , 12 ]. However, this may not show the full picture, as sociodemographic differences may also vary between situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we explored whether people with different physical distancing behavior patterns differed with respect to sociodemographic characteristics. Multiple studies indicated that sociodemographic characteristics were associated with overall adherence to physical distancing guidelines, showing for instance that women, older people, and higher educated people were more likely to distance from others [ 6 , 12 ]. However, this may not show the full picture, as sociodemographic differences may also vary between situations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, we expected that fewer people adhered to distancing guidelines as the pandemic progressed, because of an increased need for social contact, higher levels of immunity (due to vaccinations and prior infections), and possibly pandemic fatigue [ 4 , 15 ]. Sociodemographic differences in physical distancing behavior could also have become more pronounced over time and in periods with lower pandemic severity [ 12 ]. In such situations, the relative need to distance became smaller, while the need for contact increased and social norms around physical distancing relaxed.…”
Section: Introductionmentioning
confidence: 99%
“…Wear medical protective masks, disposable hats, protective clothing, protective face screens, double-layer latex gloves, waterproof isolation clothes, and shoe covers. [48][49][50][51][52][53] See Table 1.…”
Section: Personal Protectionmentioning
confidence: 99%
“…Studies conducted during the early stages of the COVID-19 pandemic yielded mixed results with some studies suggesting a decrease in PPB use (e.g. [22][23][24][25][26],…”
Section: Introductionmentioning
confidence: 99%